A Survey on Rule Based Approach for Content Confidentiality in E-Governance Applications: Computational Intelligence - Billa Sai Pranavi, Dr. G. S. Bapiraju (International Journal of Advanced Science and Technology, 2020)
Content Confidentiality has become a certifiable anxiety considering encounter day material Societies. Fragile thought epithetical an extraordinary piece epithetical private individual data a certain prevail exchanged otherwise released via untrusted parties necessitates a certain committed associations should set out over sensible substance mystery security agendas. Nowadays, countless these data prevail works (e.g., messages, messages posted exist electronic life, therapeutic administrations results, etc.) that, taking into account their unstructured & semantic nature, sets up a test considering modified data confirmation techniques. Exist this manuscript, we encounter response considering position protection apportioning content protection exist e-Governance benefits through reckoning understanding. Exist this survey we propose a novel position classification preserving calculation considering content protection exist e-Governance. Proposed estimation applies reckoning insight exist e-Governance considering content protection through techniques considering rule-based procedure commencing reckoning material & customer's current position information.